New advances in allergy immunotherapy. Issue 3 (June 2016) - Reisacher, William R.; Schwanke, Theresa
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: The present article reviews the literature on new methods for administering specific immunotherapy for the treatment of immunoglobulin E-mediated hypersensitivity to airborne and food allergens. The discussion will focus on allergen modifications, and new routes for delivering proteins to allergen-presenting cells. Recent findings: Modified allergens address the issues of supply and standardization, but also have the potential to enhance the allergenicity of the protein, while decreasing the risk of producing severe reactions. The use of immunostimulatory adjuvants and recombinant proteins has increased, whereas new technologies, such as the encapsulation of allergens into nanoparticles, have also gained much attention. New delivery routes for specific immunotherapy continue to be explored, often in combination with allergen modification strategies, in order to shorten the duration of therapy, limit adverse events, and optimize patient adherence. Safety and long-term efficacy have been demonstrated for many of these new methods, and it is clear that there are multiple ways to stimulate the immune system for the purpose of allergen desensitization. Summary: Developments in the field of specific immunotherapy for allergic disease are accelerating rapidly because of advances in technology, but also because of the recognition that this disease-modifying therapy is a well tolerated, efficacious, and cost-effective option for individuals, which can improved their quality of life in a long-term fashion. Video abstract: http://links.lww.com/COOH/A21